Analysis of oxidative stability and fatty acids profile of coconut oil and flaxseed oil blends - Nivetha, R.; Simmaky, S.; Sivakanthan, S. (The Spanish National Research Council (CSIC), 2024)
This study aimed to analyze the oxidative stability of flaxseed oil and coconut oil blends. Coconut oil: flaxseed oil was mixed at different ratios on weight basis (95:5, 90:10, 85:15, 80:20, and 75:25). The oxidative stability was measured using acid value, iodine value, peroxide value, and saponification value under accelerated oven storage and frying conditions. The fatty acid profile was determined by gas-liquid chromatography. According to the results, all blends showed acceptable oxidative stability under both conditions. They showed storage stability up to 14 months under ambient conditions. Blended oils had a more balanced SFA: MUFA: PUFA ratio than the original oils. Blending the oils at the ratio of 80:20 (coconut oil: flaxseed oil) showed the desirable omega-3 and omega-6 fatty acid composition before and after frying. Therefore, the blending of flaxseed oil with coconut oil could widen the applicability of flaxseed oil.
Keywords: Blending; Coconut oil; Flaxseed oil; Omega-3 fatty acids; Oxidation; Oxidative stability